Panorama das mudanças institucionais na cabotagem no Brasil - Barbosa, Julia dos Santos (Universidade Federal de São Carlos, 2025)
This undergraduate thesis aims to analyze the institutional structure of coastal shipping (cabotage) in Brazil, focusing on the factors that influence its performance within the national transport matrix. The research adopts the perspective of New Institutional Economics, particularly Douglass North’s theory, to understand how institutions shape incentives and condition the sector’s development. Despite its logistical, economic, and environmental advantages, cabotage in Brazil still faces significant challenges, such as market concentration, regulatory rigidity, port bureaucracy, and infrastructure shortages. Using a qualitative approach based on literature review and document analysis, the study also examines the impacts of Law No. 14.301/2022 (BR do Mar Program), which aims to stimulate the use of this transport mode through the flexibilization of vessel chartering and sector modernization. The study concludes that strengthening cabotage requires deep institutional reforms, strategic state action, and the creation of a more efficient, transparent, and competitive regulatory environment.
Overview of institutional changes in cabotage in Brazil
Keywords: Cabotagem; Instituições; Transporte aquaviário; BR do Mar; Nova economia institucional; Cabotage; Institutions; Waterway transport; New institutional economics; CIENCIAS SOCIAIS APLICADAS::ECONOMIA; 16. Paz, Justiça e Instituições Eficazes; 9. Indústria, Inovação e Infraestrutura